Association between vitamin D, VDR polymorphism and IVF outcomes - Anastasiia G. Syrkasheva; Svetlana V. Kindysheva; Vladimir E. Frankevich; Andrey E. Donnikov; Nataliia V. Dolgushina (IP Berlin A.V., 2022)
Aim. To analyze the outcomes of assisted reproductive technology (ART) cycles in patients with different levels of vitamin D. Materials and methods. The study included 100 infertile patients who applied for ART. Vitamin D levels were determined by mass spectrometry. The VDR polymorphism was evaluated using real-time PCR. Results. 50% of patients (n=50) had a sufficient level of vitamin D (group 3), 36% of patients (n=36) had an insufficient level of vitamin D (group 2), 14% of patients (n=14) had a deficiency of vitamin D (group 1). The level of vitamin D was not associated neither with baseline patients characteristics nor with embryological stage of the cycle. The clinical pregnancy rate was lower in the group 1 (vitamin D deficiency), but the difference was not significant. There was a trend to an increase of miscarriage rate in the groups of patients with vitamin D insufficiency and deficiency: 66.7% in group 1, 26.3% in group 2, and 13.6% in group 3. The live birth rate was higher in the groups of patients with normal and insufficient levels of vitamin D compared with the group of vitamin D deficiency: 46.0 and 38.9% compared to 7.1%, p=0.0821. In multivariate analysis clinical pregnancy rate was influenced by vitamin D deficiency and the genetic characteristics of the VDR gene: the presence of the G allele (FOKI-rs2228570). Conclusion. The vitamin D deficiency impairs the effectiveness of ART cycles.